Secondary battery and method for manufacturing the same
Through the use of the combined solvent method and surface active agent during the coating process of the polar sheet, the problem of "thick edge" of the coating "thick edge" was solved, and the stability and safety performance of the polar sheet were improved, and the high energy density and excellent of the battery cells were achieved. Electrical performance.
Patent Information
- Application Number
- CN202411488398.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the coating "thick edge" problem often occurs during the coating of the electrode sheet, resulting in poor stability of the electrode sheet and easy cracking of the coating, affecting the overall performance and safety of the battery.
Adopt a common solvent method, introduce low -surface tension, high -boiling organic solvents and water mixing graphite preparation of aligurne negative pole slurry to form surface tension gradient to offset the capacity of the capillary, reduce the amount of high -boiling dot solvents, and introduce surface active agents to increase viscosity and reduce Crack risk.
Effectively eliminates the "thick edge" problem of coating, improves the stability and safety performance of the pole, reduces energy consumption and production costs, and at the same time improves the energy density and electrical performance of the battery cells.
Smart Images

Figure CN119361796A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a secondary battery and a preparation method thereof. Background Art
[0002] Pole sheet manufacturing is crucial to the performance of lithium-ion batteries. The coating process is the core step to ensure the quality of pole sheets, which has a direct impact on the success or failure of subsequent processes such as rolling and die-cutting. Coating is the process of evenly applying a uniformly mixed slurry to the current collector and then drying it. The final quality of the coating is determined by a variety of factors, including slurry properties, drying conditions, and coating rate. During the coating process, a variety of defects may occur, among which excessive edge thickness (i.e., "thick edge") is a common problem (see Figure 1 ), which occurs during the drying of the negative electrode graphite slurry coating (see Figure 2 ) When the electrode is coated and rolled, the water evaporates faster at the edge due to the larger area-to-volume ratio. Under the capillary force, the slurry particles move to the edge to form a "thick edge". After drying, the thickness of the edge of the electrode increases significantly. This edge coating is several microns to more than ten microns thicker than the normal area. This results in the accumulation of larger bulges when the electrode is coated and rolled, causing the edge of the electrode roll to bulge, and in extreme cases may cause the electrode to break. In addition, the thick edge phenomenon will also cause the edge of the electrode to be subjected to higher pressure during rolling, resulting in uneven lateral density of the electrode, further affecting the overall performance and safety of the battery.
[0003] It can be seen that it is urgent to explore a more ideal method to eliminate the "thick edge" of the coating edge. Summary of the invention
[0004] The main purpose of the present invention is to provide a secondary battery and a preparation method thereof, so as to solve the problem of poor stability of the pole piece and easy cracking of the coating when solving the problem of "thick edge" of the coating during the coating process of the pole piece in the prior art.
[0005] In order to achieve the above-mentioned object, according to one aspect of the present invention, a secondary battery is provided, comprising a battery cell, wherein the battery cell comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode material coating stacked on the surface of the negative electrode current collector, wherein the negative electrode material coating is obtained by coating a negative electrode slurry on the surface of the negative electrode current collector and then drying and compacting the negative electrode slurry, wherein the negative electrode slurry comprises 2 to 5 parts by weight of a surfactant, wherein the surfactant is an anionic surfactant, and the anionic surfactant is selected from sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate , any one or more of sodium stearate, sodium fatty alcohol ether sulfate, 80 to 100 parts by weight of a solvent, the solvent comprising a first solvent and a second solvent, the first solvent being water, the second solvent being an organic solvent, the boiling point of the second solvent being 110 to 210° C., and the surface tension of the second solvent being 20 to 50 dyn / cm; the mass ratio of the second solvent to the first solvent being 1:10 to 1:2, 0.5 to 1.5 parts by weight of a dispersant, 0.6 to 1.2 parts by weight of a conductive agent, 96 to 98 parts by weight of a negative electrode active material and 1 to 2.5 parts by weight of a binder.
[0006] Furthermore, along the width direction of the above-mentioned negative electrode material coating, the negative electrode material coating includes a middle area and edge transition areas located on both sides of the middle area, the thickness of the edge transition area gradually decreases in the direction away from the middle area, the thickness of the middle area is H1, and the width of the edge transition area is L2 in the direction away from the middle area, wherein L2 / H1 is 0.004 to 0.01:1.
[0007] Furthermore, the above L2 is 1 to 2 mm, and H1 is 200 to 230 mm.
[0008] Furthermore, the second solvent is 8 to 15 parts by weight, and preferably the second solvent is selected from any one or more of ethylene glycol, ethylenediamine, butanol, acetic acid, propylene glycol and methylformamide.
[0009] Furthermore, the mass ratio of the surfactant to the second solvent is 3:20 to 5:8; and / or the viscosity of the negative electrode slurry is 6000 to 9000 Pa·s.
[0010] Furthermore, the above-mentioned negative electrode active material is selected from any one or more of graphite, silicon material, silicon-carbon material, and hard carbon; and / or the conductive agent is selected from any one or more of SP conductive agent, carbon black, carbon nanotubes, and graphene; and / or the binder is SBR binder and / or PAA binder; and / or the dispersant is CMC dispersant.
[0011] Furthermore, the negative electrode slurry includes 96-97 parts by weight of graphite, 0.8-1.0 parts by weight of SP conductive agent, 2-2.5 parts by weight of SBR binder, 1.2-1.5 parts by weight of CMC dispersant, 8-30 parts by weight of ethylene glycol, 70-92 parts by weight of deionized water and 3-4 parts by weight of sodium dodecyl sulfate.
[0012] Furthermore, the boiling point of the second solvent is 10-110° C. higher than that of water, and / or the surface tension of the second solvent is 15-50 dyn / cm lower than that of water; and / or the water is deionized water.
[0013] According to another aspect of the present invention, a method for preparing a secondary battery is provided, comprising: preparing a negative electrode slurry, coating the negative electrode slurry on a negative electrode current collector, and then drying and compacting in sequence to obtain a negative electrode; preparing a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector, and then drying and compacting in sequence to obtain a positive electrode; assembling various units including a positive electrode, a negative electrode, a separator and an electrolyte to obtain a secondary battery; the steps of preparing the above-mentioned negative electrode slurry include: step S1, dry mixing a negative electrode active material, a conductive agent and a dispersant to obtain a dry mixture; step S2, kneading the dry mixture with a part of a first solvent to obtain a kneaded product; step S3, first wet mixing the kneaded product, the remaining part of the first solvent and a second solvent to obtain a first wet mixture; step S4, second wet mixing the first wet mixture with a surfactant to obtain a second wet mixture; step S5, third wet mixing the second wet mixture with a binder to obtain a negative electrode slurry; wherein the sum of the amount of the part of the first solvent and the remaining part of the first solvent is the total amount of the first solvent.
[0014] Further, in step S1, the stirring parameters in the dry mixing process are: the revolution speed is 15-25 rpm, the stirring speed is 500-800 rpm, and the stirring time is 30-60 min; and / or, in step S2, the kneading time is 60-80 min, and the stirring parameters in the kneading process are: the revolution speed is 20-25 rpm, and the stirring speed is 300-500 rpm; and / or, in step S3, the stirring parameters in the first wet mixing process are: the revolution speed is 22-25 rpm , the stirring speed is 1000-1500rpm, and the stirring time is 90-120min; and / or, in step S4, the stirring parameters in the second wet mixing process are: the revolution speed is 22-25rpm, the stirring speed is 500-1000rpm, and the stirring time is 60-90min; and / or, in step S5, the stirring parameters in the third wet mixing process are: the revolution speed is 22-25rpm, the stirring speed is 300-600rpm, and the stirring time is 30-40min.
[0015] Applying the technical solution of the present application, the present application adopts a co-blended solvent method, that is, an organic solvent with low surface tension and high boiling point relative to water is introduced and mixed with water to prepare graphite negative electrode slurry. The co-blended solvent method starts from the inherent mechanism of the formation of the "thick edge" of the coating edge. First, a solvent with low surface tension and high boiling point relative to water is mixed with water. During the baking process of the double solvent slurry, the concentration of the second solvent at the edge during the drying process is higher than that at the middle position due to the high boiling point solvent. At this point, the coating forms a surface tension gradient from the inside to the edge, inducing the edge slurry particles to move to the inner layer, which offsets the capillary effect of the formation of the "thick edge", that is, offsets the edge aggregation effect caused by the capillary action, thereby solving the problem of the "thick edge" of the coating. However, the high boiling point solvent introduced requires a higher baking temperature and a longer baking time to dry the electrode, which makes the electrode easy to crack under high baking temperature and long baking time. In response to this technical problem, the present application introduces a surfactant. Due to the effect of the hydrophilic group and the hydrophobic group in the surfactant, it will form a uniform adsorption layer on the surface of the graphite particles, so that the graphite particles are negatively charged as a whole. The electrostatic effect and steric hindrance generated by its effective adsorption on the graphite particles effectively reduce the capillary action and the "thick edge" effect (i.e., reduce the aggregation of graphite particles at the edge), while reducing the amount of high-boiling point solvents, thereby increasing the viscosity of the slurry to an appropriate range (thus being able to eliminate the use of thickeners), thereby reducing the coating and baking temperature, significantly improving the cracking problem of the slurry during the coating process, and reducing the energy consumption caused by baking, thereby reducing costs. In addition, compared to the thinning method, the present application's method of eliminating the thick edge is not only simple to operate, but also can improve the energy density of the battery cell, and reduce the risk of lithium precipitation at the edge of the pole piece, ensuring the fit of the pole piece during the assembly process, thereby significantly improving the stability, safety and electrical performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 A schematic diagram showing an overly thick coating edge formed during the coating process of a pole piece in the prior art;
[0018] Figure 2 Shows Figure 1 Schematic diagram of the drying principle of the negative electrode coating shown;
[0019] Figure 3 A schematic diagram of a coating edge obtained by thinning the edge of a pole piece during coating provided in the prior art is shown;
[0020] Figure 4A schematic diagram showing a coating edge formed during the coating process of a pole piece provided by Example 1 of the present invention is shown;
[0021] Figure 5 Shows Figure 4 Schematic diagram of the drying principle of the negative electrode coating shown;
[0022] Figure 6 The present invention shows a process flow chart of preparing a negative electrode slurry provided in Example 1;
[0023] Figure 7 shows a distribution diagram of thickness measurement results of #1 to #5 of the present invention;
[0024] Figure 8 The distribution diagram of the measurement results of the coating thickness of the negative electrode sheets in Examples 1 to 8 of the present invention and Comparative Examples 1 to 5 is shown. DETAILED DESCRIPTION
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0026] At present, in order to solve the problem of "thick edge" of coating during coating, the commonly used strategy in the industry is to thin the edge of the pole piece during coating (see Figure 3 ), this method reduces the coating amount in the edge area of the coater to form a thinning area to alleviate the problem of excessive thickness at the edge of the coating after drying. Such a treatment can effectively avoid the bulging edge phenomenon when the pole roll is rolled up, and the problem of inconsistent lateral density caused by uneven thickness during rolling. However, for the coating thinning method, although it can eliminate the problem of thick edges of the pole pieces, reduce the protrusion of the pole piece edges, and reduce the risk of pole piece breakage. However, thinning leads to a reduction in the thickness of the coating edge area, which reduces the amount of active substances in the positive pole piece, thereby reducing the capacity of the battery cell. At the same time, the degree of thinning is difficult to control, and the equipment capacity is required to be high. The volatility of the thinning size during the production process is large. For the thinning of the edge of the negative pole piece, the N / P ratio may decrease, resulting in lithium precipitation at the edge, which directly affects the stability and safety of the battery cell. In addition, the thinning area will also cause a certain gap between the pole pieces after winding, and the pole pieces are not tightly fitted, resulting in an increase in the local internal resistance of the battery during the charging and discharging process, resulting in lithium precipitation, which affects the battery performance. In general, the thinning of the pole piece is a compromise between design and manufacturing. The thinning width should be reduced as much as possible while eliminating the "thick edge". Therefore, in response to the "thick edge" problem of the coating, the industry focuses more on how to control the thinning size more finely, hoping to minimize the thinning size while eliminating the "thick edge".
[0027] As described above, in the prior art, when solving the problem of "thick edges" of the coating during the coating process of forming the electrode, there are problems such as poor stability of the electrode and easy cracking of the coating. In order to solve this problem, the present application provides a secondary battery and a preparation method thereof.
[0028] In a typical embodiment of the present application, a secondary battery is provided, comprising a battery cell, the battery cell comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode material coating stacked on the surface of the negative electrode current collector, the negative electrode material coating is obtained by coating a negative electrode slurry on the surface of the negative electrode current collector and then drying and compacting in sequence, wherein the negative electrode slurry comprises 2 to 5 parts by weight of a surfactant, the surfactant is an anionic surfactant, and the anionic surfactant is selected from sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate , any one or more of sodium stearate, sodium fatty alcohol ether sulfate, 80 to 100 parts by weight of a solvent, the solvent comprising a first solvent and a second solvent, the first solvent being water, the second solvent being an organic solvent, the boiling point of the second solvent being 110 to 210° C., and the surface tension of the second solvent being 20 to 50 dyn / cm; the mass ratio of the second solvent to the first solvent being 1:10 to 1:2, 0.5 to 1.5 parts by weight of a dispersant, 0.6 to 1.2 parts by weight of a conductive agent, 96 to 98 parts by weight of a negative electrode active material and 1 to 2.5 parts by weight of a binder.
[0029] The present application adopts a co-blended solvent method, that is, an organic solvent with low surface tension and high boiling point relative to water is introduced and mixed with water to prepare graphite negative electrode slurry. The co-blended solvent method starts from the inherent mechanism of the formation of the "thick edge" of the coating edge. First, a solvent with low surface tension and high boiling point relative to water is mixed with water. During the baking process of the double solvent slurry, the concentration of the second solvent at the edge during the drying process is higher than that at the middle position due to the high boiling point solvent. At this point, the coating forms a surface tension gradient from the inside to the edge, inducing the edge slurry particles to move to the inner layer, which offsets the capillary effect of the formation of the "thick edge", that is, offsets the edge aggregation effect caused by the capillary action, thereby solving the problem of the "thick edge" of the coating. However, the high boiling point solvent introduced requires a higher baking temperature and a longer baking time to dry the electrode, which makes the electrode easy to crack under high baking temperature and long baking time. In response to this technical problem, the present application introduces a surfactant. Due to the effect of the hydrophilic group and the hydrophobic group in the surfactant, it will form a uniform adsorption layer on the surface of the graphite particles, so that the graphite particles are negatively charged as a whole. The electrostatic effect and steric hindrance generated by its effective adsorption on the graphite particles effectively reduce the capillary action and the "thick edge" effect (i.e., reduce the aggregation of graphite particles at the edge), while reducing the amount of high-boiling point solvents, thereby increasing the viscosity of the slurry to an appropriate range (thus being able to eliminate the use of thickeners), thereby reducing the coating and baking temperature, significantly improving the cracking problem of the slurry during the coating process, and reducing the energy consumption caused by baking, thereby reducing costs. In addition, compared to the thinning method, the present application's method of eliminating the thick edge is not only simple to operate, but also can improve the energy density of the battery cell, and reduce the risk of lithium precipitation at the edge of the pole piece, ensuring the fit of the pole piece during the assembly process, thereby significantly improving the stability, safety and electrical performance of the battery cell.
[0030] In one embodiment of the present application, along the width direction of the above-mentioned negative electrode material coating, the negative electrode material coating includes a middle area and edge transition areas located on both sides of the middle area, the thickness of the edge transition area gradually decreases in the direction away from the middle area, the thickness of the middle area is H1, and the width of the edge transition area is L2 in the direction away from the middle area, wherein L2 / H1 is 0.004 to 0.01:1.
[0031] Preferably, L2 / H1 is in the range of 0.004 to 0.01:1, for example, 0.004:1, 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1 or 0.01:1, but is not limited to the listed values, and other values not listed in the above range are also applicable. Compared with the thinning process in the prior art, the preferred L2 / H1 value helps to make the battery cell have higher safety and energy density on the basis of avoiding the problem of "thick edge" of coating.
[0032] Further, in order to improve the adaptability of the actual battery cell in the above scheme, so that the battery cell has excellent electrical performance, in one embodiment of the present application, it is preferred that the above L2 is 1 to 2 mm, for example, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm or 2 mm, but not limited to the listed values, other values not listed in the above range are also applicable. H1 is 200 to 230 mm, for example, 210 mm, 215 mm, 220 mm, 225 mm or 230 mm, but not limited to the listed values, other values not listed in the above range are also applicable.
[0033] In addition, by changing the types of the first solvent and the second solvent, and by combining the two, it can also be suitable as a solvent for the positive electrode slurry, so that the components in the positive electrode slurry can be more fully dispersed therein to obtain a uniform positive electrode slurry, and further solve the problem of "thick edges" of the coating during the positive electrode sheet coating process.
[0034] In one embodiment of the present application, the second solvent is 8 to 15 parts by weight, and the second solvent is preferably selected from any one or more of ethylene glycol, ethylenediamine, butanol, acetic acid, propylene glycol and methylformamide, preferably any one or more of ethylene glycol, propylene glycol and methylformamide.
[0035] When the proportion of the second solvent is too low, the surface tension gradient between the edge and the middle slurry during the coating and baking process is too small, and the coating is prone to "thick edge" problems. When the proportion of the second solvent is too high, the baking temperature required during the coating process is high, which is easy to cause problems such as cracking of the coating and increase costs. The type and content of the above second solvent are preferred, and the second solvent is further preferably 10 to 15 parts by weight. For example, the second solvent is 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight or 15 parts by weight, but is not limited to the listed values, and other unlisted values within the numerical range of 8 to 15 parts by weight are also applicable. It is further preferred that the second solvent is selected from any one or more of ethylene glycol, propylene glycol, and methylformamide, so that on the basis of being able to induce the edge slurry particles to move to the inner layer, the amount of the second solvent used is reduced as much as possible, thereby mitigating its effect on reducing the viscosity of the slurry.
[0036] In one embodiment of the present application, the mass ratio of the above-mentioned surfactant to the second solvent is 3:20 to 5:8; and / or the viscosity of the negative electrode slurry is 6000 to 9000 Pa·s.
[0037] The preferred mass ratio of the surfactant to the second solvent is within the above range, which not only helps to use the second solvent to form a surface tension gradient from the inside to the edge of the coating, inducing the edge slurry particles to move to the inner layer, but also helps to compensate for the deficiency of the second solvent causing the slurry viscosity to decrease, so that the above two aspects can be more fully taken into account, so that the effect of the second solvent is optimized, and then the coating "thick edge" elimination plays a significant role. At the same time, the amount of the second solvent is greatly reduced, so that the viscosity of the negative electrode slurry is increased to 6000 ~ 9000Pa · s, thereby reducing the coating baking temperature. Among them, the preferred mass ratio of the surfactant to the second solvent is 1:15 to 1:10, for example, the mass ratio of the surfactant to the second solvent is 1:15, 1:14, 1:13, 1:12, 1:11 or 1:10, but is not limited to the listed values, and other unlisted values within the numerical range of 3:20 to 5:8 are also applicable. Preferably, the viscosity of the negative electrode slurry is 6500-8500 Pa·s, for example, the viscosity of the negative electrode slurry is 6500 Pa·s, 7000 Pa·s, 7500 Pa·s, 8000 Pa·s or 8500 Pa·s, but is not limited to the listed values, and other unlisted values within the numerical range of 6000-9000 Pa·s are also applicable.
[0038] In one embodiment of the present application, the above-mentioned negative electrode active material is selected from any one or more of graphite, silicon material, silicon-carbon material, and hard carbon; and / or the conductive agent is selected from any one or more of SP conductive agent, carbon black, carbon nanotubes, and graphene; and / or the binder is SBR binder and / or PAA binder; and / or the dispersant is CMC dispersant.
[0039] The above preferred negative electrode active materials, conductive agents, binders and dispersants are more conducive to their coordination with the above types of solvents, thereby reducing the risk of "thick edges" of the entire negative electrode slurry during the coating process.
[0040] Furthermore, in order to improve the synergistic effect between the components in the negative electrode slurry, in one embodiment of the present application, the negative electrode slurry preferably includes 96-97 parts by weight of graphite, 0.8-1.0 parts by weight of SP conductive agent, 2-2.5 parts by weight of SBR binder, 1.2-1.5 parts by weight of CMC dispersant, 8-30 parts by weight of ethylene glycol, 70-92 parts by weight of deionized water and 3-4 parts by weight of sodium dodecyl sulfate. For example, the negative electrode slurry is 96 parts by weight, 96.5 parts by weight or 97 parts by weight of graphite; the SP conductive agent is 0.8 parts by weight, 0.9 parts by weight or 1.0 parts by weight; the SBR binder is 2.1 parts by weight, 2.2 parts by weight, 2.3 parts by weight, 2.4 parts by weight or 2.5 parts by weight; the CMC dispersant is 1.2 parts by weight, 1.3 parts by weight, 1.4 parts by weight or 1.5 parts by weight; preferably, ethylene glycol is 10 to 30 parts by weight, for example, ethylene glycol is 10 parts by weight, 12 parts by weight, 14 parts by weight, 16 parts by weight, 18 parts by weight. parts by weight, 20 parts by weight, 22 parts by weight, 24 parts by weight, 26 parts by weight, 28 parts by weight or 30 parts by weight; preferably, deionized water is 75-85 parts by weight, for example, deionized water is 75 parts by weight, 76 parts by weight, 77 parts by weight, 78 parts by weight, 79 parts by weight, 80 parts by weight, 81 parts by weight, 82 parts by weight, 83 parts by weight, 84 parts by weight or 85 parts by weight; polyethylene glycol is 3 parts by weight, 3.5 parts by weight or 4 parts by weight; but it is not limited to the listed values, and other unlisted values within the numerical ranges of the above components are equally applicable.
[0041] In one embodiment of the present application, the boiling point of the second solvent is 10-110° C. higher than that of water, and / or the surface tension of the second solvent is 15-50 dyn / cm lower than that of water; and / or the water is deionized water.
[0042] The second solvent having the above-mentioned boiling point difference and surface tension value with the first solvent is preferred, which helps to reduce the negative impact of the reduction in slurry viscosity caused by the second solvent as much as possible on the basis of the purpose of inducing the edge slurry particles to move to the inner layer by the second solvent. Specifically, if the boiling point of the second solvent is too higher than that of water, the solvent is difficult to evaporate. If the boiling point of the second solvent is too lower than that of water, the viscosity of the negative electrode slurry is too low, and it is difficult to achieve its coating on the current collector. Therefore, it is preferred that the boiling point of the second solvent is 50 to 100°C higher than the boiling point of water, for example, the boiling point of the second solvent is 50°C, 60°C, 70°C, 80°C, 90°C or 100°C higher than the boiling point of water, but is not limited to the listed values, and other unlisted values within the numerical range of 10 to 110°C are also applicable. If the surface tension of the second solvent is higher than that of water, the problem of "thick edge" of the negative electrode coating cannot be solved. If the surface tension of the second solvent is too lower than that of water, the viscosity of the negative electrode slurry is too low, and it is difficult to implement the coating of the negative electrode slurry. Therefore, it is preferred that the surface tension of the second solvent is 20 to 45 dyn / cm lower than that of water. For example, the surface tension of the second solvent is 20 dyn / cm, 25 dyn / cm, 30 dyn / cm, 35 dyn / cm, 40 dyn / cm or 45 dyn / cm lower than that of water, but is not limited to the listed values, and other unlisted values within the numerical range of 15 to 50 dyn / cm are also applicable.
[0043] In another typical embodiment of the present application, a method for preparing the above-mentioned secondary battery is provided, comprising: preparing a negative electrode slurry, coating the negative electrode slurry on a negative electrode current collector, and then drying and compacting in sequence to obtain a negative electrode; preparing a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector, and then drying and compacting in sequence to obtain a positive electrode; assembling each unit including a positive electrode, a negative electrode, a separator and an electrolyte to obtain a secondary battery; wherein the preparation steps of the negative electrode slurry include: step S1, mixing a negative electrode active material, a conductive agent The step S2 comprises kneading the dry mixture with a part of the first solvent to obtain a kneaded product; the step S3 comprises first wet mixing of the kneaded product, the remaining part of the first solvent and the second solvent to obtain a first wet mixture; the step S4 comprises second wet mixing of the first wet mixture with a surfactant to obtain a second wet mixture; the step S5 comprises third wet mixing of the second wet mixture with a binder to obtain a negative electrode slurry; wherein the sum of the amount of the part of the first solvent and the remaining part of the first solvent used is the total amount of the first solvent.
[0044] The preferred step-by-step mixing process allows the components in the negative electrode slurry to be mixed more evenly, thereby making the coating formed after the slurry is applied more uniform and making the problem of "thick edges" of the coating more effectively eliminated, thereby making the battery cell have excellent electrical properties.
[0045] In one embodiment of the present application, in the above step S1, the stirring parameters in the dry mixing process are: the revolution speed is 15-25 rpm, the stirring speed is 500-800 rpm, and the stirring time is 30-60 min; and / or, in step S2, the kneading time is 60-80 min, and the stirring parameters in the kneading process are: the revolution speed is 20-25 rpm, and the stirring speed is 300-500 rpm; and / or, in step S3, the stirring parameters in the first wet mixing process are: the revolution speed is 22-2 5rpm, the stirring speed is 1000-1500rpm, and the stirring time is 90-120min; and / or, in step S4, the stirring parameters in the second wet mixing process are: the revolution speed is 22-25rpm, the stirring speed is 500-1000rpm, and the stirring time is 60-90min; and / or, in step S5, the stirring parameters in the third wet mixing process are: the revolution speed is 22-25rpm, the stirring speed is 300-600rpm, and the stirring time is 30-40min.
[0046] The preferred control of the stirring parameters in each of the above mixing steps enables each component to obtain a better mixing effect with adaptive stirring parameters after being added, thereby obtaining a uniform negative electrode slurry. This can ensure the uniformity of the rolling process of the pole piece, reduce the stress concentration of the pole piece due to uneven rolling, and effectively reduce the undesirable problems such as the rolling wavy edge of the pole piece. At the same time, the coating thickness obtained by this method is uniform, and for the subsequent assembly process, the fit between the pole pieces is greatly improved, which significantly improves the performance of the battery cell. Wherein, in the above step S1, the stirring parameters in the dry mixing process are: for example, the revolution speed is 15rpm, 20rpm or 25rpm, the stirring speed is 500rpm, 600rpm, 700rpm or 800rpm, and the stirring time is 30min, 40min, 50min or 60min; in step S2, the kneading time is 60min, 70min or 80min, and the stirring parameters in the kneading process are: the revolution speed is 20rpm, 21rpm, 22rpm, 23rpm, 24rpm or 25rpm, and the stirring speed is 300rpm, 400rpm or 500rpm; in step S3, the stirring parameters in the first wet mixing process are: the revolution speed is 22rpm, 23rpm, 24rpm or 25rpm, and the stirring speed is 1000rpm, 1100rpm, 120 0rpm, 1300rpm, 1400rpm or 1500rpm, and the stirring time is 90min, 100min, 110min or 120min; in step S4, the stirring parameters in the second wet mixing process: the revolution speed is 22rpm, 23rpm, 24rpm or 25rpm, the stirring speed is 500rpm, 600rpm, 700rpm, 800rpm, 900rpm or 1000rpm, and the stirring time is 60min, 70min, 80min or 90min; in step S5, the stirring parameters in the third wet mixing process: the revolution speed is 22rpm, 23rpm, 24rpm or 25rpm, the stirring speed is 300rpm, 400rpm, 500rpm or 600rpm, and the stirring time is 30min, 35min or 40min. However, it is not limited to the listed values, and other unlisted values within the numerical range of the above conditions are also applicable.
[0047] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.
[0048] The preferred ratio of the first solvent to the second solvent is explored, as shown in Table 1.
[0049] Table 1
[0050]
[0051]
[0052] The components #1 to #5 are mixed according to the following mixing process to obtain negative electrode slurries #1 to #5.
[0053] The above amount of graphite powder, conductive agent and dispersant are put into the mixing cylinder for dry mixing for 30 minutes, with a stirring revolution speed of 15rpm and a dispersion speed of 500rpm. Thereafter, 50 parts of deionized water are added for kneading and stirring for 60min, with a stirring revolution speed of 20rpm and a dispersion speed of 300rpm. Then, the second solvent and the remaining deionized water are added for high-speed dispersion, with a stirring revolution speed of 22rpm and a dispersion speed of 1000rpm. Finally, a binder is added and stirred for 30min, with a stirring revolution speed of 22rpm and a dispersion speed of 500rpm, to finally obtain #1 to #5 negative electrode slurries.
[0054] Coating: According to the design requirements of the battery cell, #1 to #5 negative electrode slurries are coated on the copper foil respectively to obtain #1 to #5 negative electrode sheets. The thickness measurement results of #1 to #5 negative electrode sheets are shown in the distribution diagram. Figure 7 As shown, the thickness of the #1 to #5 negative electrode plates at different electrode plate positions are shown in Table 2.
[0055] Table 2
[0056]
[0057]
[0058]
[0059] Combined with Table 1 and Figure 7 It can be seen that the preferred mass ratio of ethylene glycol to deionized water is 1:10 to 1:2.
[0060] On the basis of the preferred mass ratio of ethylene glycol to deionized water of 1:10 to 1:2, the effect of surfactant on the coating thickness of the negative electrode sheet was investigated, as shown in Table 3.
[0061] Table 3
[0062]
[0063] Refer to the following mixing process (also refer to Figure 6 (See the process flow chart for preparing the negative electrode slurry shown in FIG. 5 ) After mixing the components in Examples 1 to 5, the negative electrode slurries in Examples 1 to 5 are obtained.
[0064] The above amount of graphite powder, conductive agent and dispersant are put into the mixing cylinder and dry mixed for 30 minutes, with a stirring revolution speed of 15rpm and a dispersion speed of 500rpm. Thereafter, 50 parts of deionized water are added for kneading and stirring for 60min, with a stirring revolution speed of 20rpm and a dispersion speed of 300rpm. Then, the second solvent and the remaining deionized water are added and dispersed at high speed for 90min, with a stirring revolution speed of 22rpm and a dispersion speed of 1000rpm. Thereafter, sodium lauryl sulfate is added, and stirred for 60min at a revolution speed of 22rpm and a dispersion speed of 1000rpm. Finally, a binder is added and stirred for 30min, with a stirring revolution speed of 22rpm and a dispersion speed of 500rpm, to finally obtain the negative electrode slurry in Examples 1 to 5.
[0065] Coating: According to the design requirements of the battery cell, the negative electrode slurries of Examples 1 to 5 are coated on copper foils respectively to obtain negative electrode sheets of Examples 1 to 5, wherein the schematic diagram of the coating edge formed during the coating process of Example 1 is as shown in Figure 4 As shown, the schematic diagram of the drying principle of the negative electrode coating of Example 1 is as follows Figure 5 shown.
[0066] Example 6
[0067] The difference from Example 3 is that the second solvent is methylformamide, which has a boiling point 82.5° C. higher than that of deionized water and a surface tension 13.62 dyn / cm lower than that of water, and finally a negative electrode sheet is obtained.
[0068] Example 7
[0069] The difference from Example 3 is that the above amount of graphite powder, conductive agent and dispersant are put into the mixing cylinder and dry mixed for 60 minutes, the stirring revolution speed is 25rpm, and the dispersion speed is 800rpm. Thereafter, 50 parts of deionized water are added for kneading and stirring for 80min, the stirring revolution speed is 25rpm, and the dispersion speed is 500rpm. Then, the second solvent and the remaining deionized water are added and dispersed at high speed for 120min, the stirring revolution speed is 25rpm, and the dispersion speed is 1500rpm. Finally, sodium dodecyl sulfate is added, and stirred for 90min at a revolution speed of 25rpm and a dispersion speed of 500rpm. Finally, a binder is added and stirred for 40min, the stirring revolution speed is 25rpm, and the dispersion speed is 300rpm, to obtain the negative electrode slurry of Example 6, and finally the negative electrode sheet is obtained.
[0070] Example 8
[0071] The difference from Example 3 is that 96 parts of silicon-carbon material (negative electrode active material), 0.8 parts of SP (conductive agent), 2 parts of SBR (binder), 1.2 parts of CMC (dispersant), 25.71 parts of ethylene glycol (second solvent), 64.29 parts of deionized water, and 1.5 parts of sodium dodecyl sulfate are used to finally obtain a negative electrode sheet.
[0072] Comparative Example 1
[0073] Negative electrode slurry preparation:
[0074] The raw materials for preparing the negative electrode slurry were weighed according to the following weight portions: 96 parts of graphite powder (negative electrode active material), 0.8 parts of SP (conductive agent), 2 parts of SBR (binder), 1.2 parts of CMC (dispersant), 20.77 parts of ethylene glycol (second solvent), 69.23 parts of deionized water, and 2 parts of polyethylene glycol.
[0075] The above amount of graphite powder, conductive agent and dispersant were put into a mixing cylinder and dry mixed for 30 minutes, with a stirring revolution speed of 15 rpm and a dispersion speed of 500 rpm. Thereafter, 50 parts of deionized water were added for kneading and stirring for 60 minutes, with a stirring revolution speed of 20 rpm and a dispersion speed of 300 rpm. After that, the second solvent and the remaining deionized water were added for high-speed dispersion, with a stirring revolution speed of 22 rpm and a dispersion speed of 1000 rpm. Finally, a binder and a thickener were added and stirred for 30 minutes, with a stirring revolution speed of 22 rpm and a dispersion speed of 500 rpm, to finally obtain the negative electrode slurry of Comparative Example 1.
[0076] Coating:
[0077] According to the design requirements of the battery cell, the negative electrode slurry of Comparative Example 1 is coated on the copper foil without thinning treatment to obtain the negative electrode sheet of Comparative Example 1.
[0078] Comparative Example 2
[0079] Negative electrode slurry preparation:
[0080] The negative electrode slurry raw materials were weighed according to the following weight parts: 96 parts of graphite powder (negative electrode active material), 0.8 parts of SP (conductive agent), 2 parts of SBR (binder), 1.2 parts of CMC (dispersant), and 90 parts of deionized water.
[0081] The above amount of graphite powder, conductive agent and dispersant were put into a mixing cylinder and dry mixed for 30 minutes, with a stirring revolution speed of 15 rpm and a dispersion speed of 500 rpm. Thereafter, 50 parts of deionized water were added for kneading and stirring for 60 minutes, with a stirring revolution speed of 20 rpm and a dispersion speed of 300 rpm. After that, the remaining deionized water was added for high-speed dispersion, with a stirring revolution speed of 22 rpm and a dispersion speed of 1000 rpm. Finally, a binder was added and stirred for 30 minutes, with a stirring revolution speed of 22 rpm and a dispersion speed of 500 rpm, to finally obtain the negative electrode slurry of Comparative Example 1.
[0082] Coating:
[0083] According to the design requirements of the battery cell, the negative electrode slurry of comparative example 2 is coated on the copper foil, and the edge is thinned during the coating process to obtain the negative electrode sheet of comparative example 2. The schematic diagram of the coating edge is as follows: Figure 3 shown.
[0084] Comparative Example 3
[0085] The difference from Example 1 is that the total weight of ethylene glycol and deionized water is 90 parts, the mass ratio of ethylene glycol to deionized water is 3:1, and finally a negative electrode sheet is obtained.
[0086] Comparative Example 4
[0087] The difference from Example 1 is that the total weight of ethylene glycol and deionized water is 90 parts, the mass ratio of deionized water to ethylene glycol is 11:1, and finally a negative electrode sheet is obtained.
[0088] Comparative Example 5
[0089] The difference from Example 1 is that the second solvent is ethanol (boiling point 78.5° C., surface tension 24.05 dyn / cm), and finally a negative electrode sheet is obtained.
[0090] The distribution diagram of the thickness measurement results of the negative electrode sheets of Examples 1 to 8 and Comparative Examples 1 to 5 is as follows: Figure 8 The thickness of the negative electrode sheets of Examples 1 to 7 at different electrode sheet positions is shown in Table 4, and the thickness of the negative electrode sheets of Example 8 and Comparative Examples 1 to 5 at different electrode sheet positions is shown in Table 5.
[0091] Table 4
[0092]
[0093]
[0094]
[0095] Table 5
[0096]
[0097]
[0098] Performance Test:
[0099] Pole piece TD direction thickness test: Use a micrometer to measure the pole piece thickness every 5mm along the TD direction of the coated pole piece. Measure three values at each point and calculate the average value. Summarize the thickness of all points and make a graph.
[0100] The viscosity of the negative electrode slurry was tested by a rotational viscometer. The test results are shown in Table 6.
[0101] Test of L1, L2, H1 and H2: Use micrometer to measure and calculate the ratio of L1 to H1 (L1 / H1) and the ratio of L2 to H1 (L2 / H1). The results are shown in Table 1, where L1 represents the width of the thick edge area of the negative electrode coating, and H2 represents the maximum thickness of the thick edge area of the negative electrode coating. Figure 1 shown.
[0102] The sodium iron phosphate positive electrode, the separator and the negative electrode obtained in the above embodiments and comparative examples are stacked in sequence, and then assembled into a battery cell by winding or lamination. An electrolyte (lithium hexafluorophosphate + solvent, the solvent is ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1) is injected into the battery cell. The battery cell is placed in an aluminum-plastic film, the pole ears are welded or laser welded, and then sealed and formed to obtain a soft-pack lithium-ion battery with a nominal capacity of 2.3Ah. The discharge specific capacity of the lithium-ion battery is tested at 0.5P, and the test results are listed in Table 6.
[0103] Table 6
[0104]
[0105] Combining Table 3 and Figure 8 It can be seen that, compared with the other embodiments in which the second solvent is excessive or the surfactant is excessive, the negative electrode slurry formula of Embodiment 3 not only ensures the elimination of the "thick edge" during the coating process, but also reduces the use of the second solvent by adding an appropriate amount of surfactant, thereby ensuring the coating performance of the negative electrode slurry.
[0106] It can be seen from the data in Table 6 that the methods of Examples 1 to 8 not only solve the problem of "thick edges" of the coating, but also ensure that the lithium-ion battery has a higher discharge capacity and stability.
[0107] Although Comparative Example 1 can achieve the effect of eliminating the "thick edge", the amount of the second solvent used is large and a thickener is introduced, which reduces the coating performance and energy density of the slurry. Comparative Example 2 is a traditional method of eliminating the "thick edge" by thinning, which has the risk of edge lithium precipitation, greatly reducing the cycle performance and safety performance of the battery cell. In Comparative Examples 3 and 4, the proportion of the second solvent is not within the appropriate range, resulting in poor coating performance of the negative electrode slurry or poor effect of eliminating the "thick edge". Comparative Example 5 uses a second solvent that does not meet the requirements, and the "thick edge" formed during the coating process cannot be eliminated. In actual production, the negative electrode slurries prepared in the above comparative examples cannot simultaneously achieve the characteristics of excellent coating performance and significant effect of eliminating the "thick edge".
[0108] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0109] The present application adopts a co-blended solvent method, that is, an organic solvent with low surface tension and high boiling point relative to water is introduced and mixed with water to prepare graphite negative electrode slurry. The co-blended solvent method starts from the inherent mechanism of the formation of the "thick edge" of the coating edge. First, a solvent with low surface tension and high boiling point relative to water is mixed with water. During the baking process of the double solvent slurry, the concentration of the second solvent at the edge during the drying process is higher than that at the middle position due to the high boiling point solvent. At this point, the coating forms a surface tension gradient from the inside to the edge, inducing the edge slurry particles to move to the inner layer, which offsets the capillary effect of the formation of the "thick edge", that is, offsets the edge aggregation effect caused by the capillary action, thereby solving the problem of the "thick edge" of the coating. However, the high boiling point solvent introduced requires a higher baking temperature and a longer baking time to dry the electrode, which makes the electrode easy to crack under high baking temperature and long baking time. In response to this technical problem, the present application introduces a surfactant. Due to the effect of the hydrophilic group and the hydrophobic group in the surfactant, it will form a uniform adsorption layer on the surface of the graphite particles, so that the graphite particles are negatively charged as a whole. The electrostatic effect and steric hindrance generated by its effective adsorption on the graphite particles effectively reduce the capillary action and the "thick edge" effect (i.e., reduce the aggregation of graphite particles at the edge), while reducing the amount of high-boiling point solvents, thereby increasing the viscosity of the slurry to an appropriate range (thus being able to eliminate the use of thickeners), thereby reducing the coating and baking temperature, significantly improving the cracking problem of the slurry during the coating process, and reducing the energy consumption caused by baking, thereby reducing costs. In addition, compared to the thinning method, the present application's method of eliminating the thick edge is not only simple to operate, but also can improve the energy density of the battery cell, and reduce the risk of lithium precipitation at the edge of the pole piece, ensuring the fit of the pole piece during the assembly process, thereby significantly improving the stability, safety and electrical performance of the battery cell.
[0110] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A secondary battery, comprising a battery cell, wherein the battery cell comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein: The negative electrode comprises a negative electrode current collector and a negative electrode material coating layered on the surface of the negative electrode current collector, wherein the negative electrode material coating is obtained by coating a negative electrode slurry on the surface of the negative electrode current collector, followed by drying and compacting, wherein the negative electrode slurry comprises: 2 to 5 parts by weight of a surfactant, wherein the surfactant is an anionic surfactant, and the anionic surfactant is selected from any one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium stearate, and sodium fatty alcohol ether sulfate; 80 to 100 parts by weight of a solvent, wherein the solvent comprises a first solvent and a second solvent, wherein the first solvent is water, the second solvent is an organic solvent, the boiling point of the second solvent is 110 to 210° C., the surface tension of the second solvent is 20 to 50 dyn / cm, and the mass ratio of the second solvent to the first solvent is 1:10 to 1:2; 0.5 to 1.5 parts by weight of a dispersant; 0.6 to 1.2 parts by weight of a conductive agent; 96-98 parts by weight of negative electrode active material; 1 to 2.5 parts by weight of a binder.
2. The secondary battery according to claim 1, characterized in that: Along the width direction of the negative electrode material coating, the negative electrode material coating includes a middle area and edge transition areas located on both sides of the middle area, the thickness of the edge transition area gradually decreases in the direction away from the middle area, the thickness of the middle area is H1, and the width of the edge transition area in the direction away from the middle area is L2, wherein L2 / H1 is 0.004 to 0.01:
1.
3. The secondary battery according to claim 2, characterized in that: The L2 is 1 to 2 mm, and the H1 is 200 to 230 mm.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The second solvent is 8 to 15 parts by weight, and preferably the second solvent is selected from any one or more of ethylene glycol, ethylenediamine, butanol, acetic acid, propylene glycol and methylformamide.
5. The secondary battery according to claim 4, characterized in that: The mass ratio of the surfactant to the second solvent is 3:20 to 5:8; and / or the viscosity of the negative electrode slurry is 6000 to 9000 Pa·s.
6. The secondary battery according to any one of claims 1 to 3, characterized in that: The negative electrode active material is selected from any one or more of graphite, silicon material, silicon-carbon material, and hard carbon; and / or the conductive agent is selected from any one or more of SP conductive agent, carbon black, carbon nanotubes, and graphene; and / or the binder is SBR binder and / or PAA binder; and / or the dispersant is CMC dispersant.
7. The secondary battery according to claim 6, characterized in that: The negative electrode slurry includes 96-97 parts by weight of the graphite, 0.8-1.0 parts by weight of the SP conductive agent, 2-2.5 parts by weight of the SBR binder, 1.2-1.5 parts by weight of the CMC dispersant, 8-30 parts by weight of ethylene glycol, 70-92 parts by weight of deionized water and 3-4 parts by weight of the sodium dodecyl sulfate.
8. The secondary battery according to any one of claims 1 to 3, characterized in that: The boiling point of the second solvent is 10-110° C. higher than that of the water, and / or the surface tension of the second solvent is 15-50 dyn / cm lower than that of the water; and / or the water is deionized water.
9. A method for preparing the secondary battery according to any one of claims 1 to 8, comprising: Prepare negative electrode slurry, apply the negative electrode slurry on the negative electrode current collector, and then dry and compact it to obtain a negative electrode; Prepare a positive electrode slurry, apply the positive electrode slurry on a positive electrode current collector, and then sequentially dry and compact to obtain a positive electrode; Assembling the units including the positive electrode, the negative electrode, the separator and the electrolyte to obtain a secondary battery; Characterized in that, the steps of preparing the negative electrode slurry include: Step S1, dry-mixing the negative electrode active material, the conductive agent and the dispersant to obtain a dry mixture; Step S2, kneading the dry mixture with a portion of the first solvent to obtain a kneaded product; Step S3, performing a first wet mixing of the kneaded product, the remaining part of the first solvent and the second solvent to obtain a first wet mixture; Step S4, performing a second wet mixing on the first wet mixture and a surfactant to obtain a second wet mixture; Step S5, performing a third wet mixing of the second wet mixture and a binder to obtain a negative electrode slurry; The sum of the usage of the part of the first solvent and the remaining part of the first solvent is the total amount of the first solvent.
10. The preparation method according to claim 9, characterized in that: In the step S1, the stirring parameters in the dry mixing process are: the revolution speed is 15-25 rpm, the stirring speed is 500-800 rpm, and the stirring time is 30-60 min; and / or, in the step S2, the kneading time is 60-80 min, and the stirring parameters in the kneading process are: the revolution speed is 20-25 rpm, and the stirring speed is 300-500 rpm; and / or, in the step S3, the stirring parameters in the first wet mixing process are: the revolution speed is 22-25 rpm , the stirring speed is 1000-1500rpm, and the stirring time is 90-120min; and / or, in step S4, the stirring parameters in the second wet mixing process are: the revolution speed is 22-25rpm, the stirring speed is 500-1000rpm, and the stirring time is 60-90min; and / or, in step S5, the stirring parameters in the third wet mixing process are: the revolution speed is 22-25rpm, the stirring speed is 300-600rpm, and the stirring time is 30-40min.
Citation Information
Cited By
Negative electrode slurry and preparation method thereof, battery negative electrode plate, secondary battery and electric equipment
CN118231607A
Negative electrode slurry and preparation method, battery negative electrode sheet, secondary battery, and electric device
CN118231607B